Retinoic acid grafted to hyaluronan for skin delivery: Synthesis, stability studies, and biological evaluation. (1st March 2020) - Huerta-Ángeles, Gloria; Brandejsová, Martina; Štěpán, Petr; Pavlík, Vojtěch; Starigazdová, Jana; Orzol, Paulina; Kopecká, Kateřina; Halamková, Pavlína; Kulhánek, Jaromír; Velebný, Vladimír
Graphical abstract: Highlights: The stability of HA-ATRA is a function of the degree of substitution. The use of morin increased the photostability of HA-ATRA. HA-ATRA downregulates the proinflammatory cytokines IL-6 and IL-8. HA-ATRA demonstrates ability to penetrate through epidermis and dermis. The genomic activity of retinoic acid is kept after conjugation to HA. Abstract: All-trans retinoic acid (ATRA) was grafted to hyaluronan (HA) via esterification. The reaction was mediated by mixed anhydrides. A perfect control of the degree of substitution (0.5–7.5%) was obtained by varying the molar ratio of retinoic acid in the feed. The degree of substitution plays a significant role in the long-term stability. The photodegradation of HA-ATRA upon UVA irradiation resulted in β-ionone, β-cyclocitral and 5, 6-epoxy-( E )-retinoic acid. The photostability of the conjugate had increased with the combination with morin. The chemical structure of HA-ATRA and its degradation products was elucidated using NMR spectroscopy, SEC-MALLS, and gas chromatography–mass spectrometry (GC–MS). ATRA did not loss its biological activity after conjugation, as demonstrated by gene expression. The derivative was able to penetrate across the stratum corneum. Besides, HA-ATRA downregulated the expression of anti-inflammatory interleukins 6 and 8. HA-ATRA would be expected to be used for transdermal drug delivery or cosmetics.